178 Phase 2 trial of induction therapy with anti-CD20 (Rituximab) followed by maintenance therapy with anti-BAFF (Belimumab) in patients with active lupus nephritis. (April 2019) - Aranow, Cynthia; DallEra, Maria C; Byron, Margaret; Ding, Linna; Smilek, Dawn; Diamond, Betty; Wofsy, David
Abstract : Background: Despite case series suggesting efficacy, controlled trials of anti-CD20 in lupus and lupus nephritis (LN) have not meet their primary endpoints (Arthritis Rheum 2012;64:1215 and 2013;65:2368). A potential explanation is the observation that serum BAFF levels are elevated after treatment with rituximab and may lead to disease flare by facilitating maturation of and re-population with autoreactive B cells. The CALIBRATE study (NCT 02260934) was designed to test this hypothesis, to determine whether addition of anti-BAFF (belimumab) could enhance the clinical effects of anti-CD20 (rituximab), and assess safety of the combination. Methods: Forty-three patients with active LN despite conventional treatment were enrolled in a prospective randomized open-label trial that compared two therapeutic strategies. All subjects received iv rituximab (1000 mg), CTX (750 mg), and methylprednisolone (100 mg) at wks 0 and 2, followed by 40 mg/d prednisone with taper to 10 mg/d by wk 12. At wk 4, subjects were randomized to belimumab (10 mg/kg iv at wks 4, 6, 8 and then every 4 wks) plus prednisone (n=21) (RCB) or prednisone alone (RC) (n=22). Complete response (CR) was defined as: (i) urine protein:creatinine ratio (UPCR) <0.5; (ii) eGFR 120 or, if <120, eGFR >80% of screening; and (iii) prednisone dose of 10 mg/d. Partial response (PR) differed only in the UPCR criterion (>50% reduction). Results: The clinical outcome at wk 48 was similar in both groups: CR was 38% in the belimumab group (RCB) and 32% in the control group (RC). The frequency of subjects with serious infections was also similar between groups. B cell depletion occurred in both groups by wk 12, but the pace of repopulation was delayed in the RCB group. However, median IgG levels remained within the normal range in both groups. Mechanistic analyses of circulating B cells at week 48 showed differences in the relative proportions of B cell subpopulations between RC and RCB groups and fewer ANA +B cells in the RCB group (figure 1 ). Conclusions: Treatment with anti-BAFF following anti-CD20 did not improve clinical outcome at week 48; (ii) anti-BAFF delayed blood B cell reconstitution following B cell depletion; (iii) anti-BAFF following anti-CD20 was not associated with hypogammaglobulinemia or an increase in serious infections and (iv) the reconstituted B cell populations differed between the RCB and RC groups. Further analyses at 96 weeks will address how anti-BAFF therapy affects quantitative and qualitative recovery of B cells as well as long-term clinical outcome. Funding Source(s): Conducted by ITN with support from NIAID (UM1AI109565) and Genentech.